Selection of patients for liver transplantation and allocation of donated livers in the UK. Issue 2 (25th September 2007) - Neuberger, J; Gimson, A; Davies, M; Akyol, M; O'Grady, J; Burroughs, A; Hudson, M; ,; ,
Abstract : Background: The increasing shortfall between the number of patients who would benefit from liver transplantation and the availability of donor livers means that rationing has to occur. The processes of selection of patients for transplantation and for allocation of donor livers should be done according to ethical and, where possible, evidence-based criteria so that there is clarity and that the competing requirements of equity, justice, utility and benefit can be balanced. Methods: To achieve these goals for patients in the United Kingdom in need of transplantation, we have developed guidelines for the selection of patients to the national waiting list based on the risk of death without a transplant and the ability of the procedure to improve the recipient's quality of life. Guidelines have been developed for both those with acute liver failure and chronic liver disease. Allocation will depend on matching of the donor liver to the recipient. Results: The proposed system, to be introduced into the UK compares with some other systems, where different models for selection and allocation have been introduced.